Bibliometric Analysis using R Studio: Sixteen Years of Education for Sustainable Development Studies in Science Learning - Gita Nurul Puspita; Ari Widodo; Siti Sriyati; Achmad Samsudin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study investigates the trends, contributions, and impact of research in the field of Education for Sustainable Development (ESD) in science learning through a bibliometric analysis of Scopus data. The Bibliometrix R package was used as the primary tool for analysis, with visualization supported by Microsoft Excel. The analysis reveals consistent growth in research output, with Indonesia identified as the leading contributor and Universitas Pendidikan Indonesia as the top-performing institution. Based on significant publications in high-impact journals, the most influential author is Ingo Eilks. The study recorded publication peaks in 2022 and 2024, possibly driven by the increasing urgency to address sustainability issues. The findings highlight the importance of international collaboration and continuous adaptation to emerging trends. These insights provide a comprehensive overview of research trends and impacts in ESD and offer straightforward directions for future research development, particularly in the context of global collaboration and responses to evolving sustainability challenges.